1961
DOI: 10.4141/cjps61-080
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Four Irrigated Pasture Mixtures Under Grazing by Sheep

Abstract: Four herbage mixtures with two levels of fertilizer application were compared for 6 consecutive years under grazing by sheep. The most satisfactory mixture with respect to yield, persistence, and stability was one of orchardgrass, Dactylis glomerata L., smooth bromegrass, Bromus inermis Leys., creeping red fescue, Festuca rubra L., and ladino clover, Trifolium repens L. The same mixture of grasses without clover was lower yielding even with annual applications of 78 pounds of nitrogen and 48 pounds of P2O5 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1966
1966
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The botanical composition of complex mixtures changes with time and is influenced mainly by the environment and grazing management (Belesky et al, 2002b(Belesky et al, , 2002a. Botanical shifts may influence forage nutritive value and make complex mixtures more difficult to manage (Crosthwaite et al, 1996;Sleugh et al, 2000;Wilson and Clark, 1960;Belesky et al, 1999). In simple grass-legume mixtures it was found that the grass-to-legume proportion strongly influenced crude protein (CP) and neutral detergent fiber (NDF) (Sheaffer et al, 1990;Zemenchik et al, 2002).…”
mentioning
confidence: 99%
“…The botanical composition of complex mixtures changes with time and is influenced mainly by the environment and grazing management (Belesky et al, 2002b(Belesky et al, , 2002a. Botanical shifts may influence forage nutritive value and make complex mixtures more difficult to manage (Crosthwaite et al, 1996;Sleugh et al, 2000;Wilson and Clark, 1960;Belesky et al, 1999). In simple grass-legume mixtures it was found that the grass-to-legume proportion strongly influenced crude protein (CP) and neutral detergent fiber (NDF) (Sheaffer et al, 1990;Zemenchik et al, 2002).…”
mentioning
confidence: 99%
“…Tall fescue is considered to be somewhat low in palatability (1,8,16), and the use of legumes with the grass has been shown to result in improved animal performance (3,18,23). But tall fescue is a vigorous; aggressive plant in mos.t of the area where it is widely grown and maintenance of legumes in association may be difficult ( 6,7,25).…”
mentioning
confidence: 99%